BaZrO3 and Cs-BaZrO3 catalysed transesterification of Millettia Pinnata oil and optimisation of reaction variables by response surface Box-Behnken design. (April 2019) - Kumar, Dipesh; Singh, Bhaskar
Abstract: Perovskite BaZrO3 was synthesised via a relatively mild solid-state reaction route by using nitrate precursors. Thermal behaviour, the presence of crystalline phases and functional groups, specific surface area, microstructural characteristics, elemental composition, and basic strength of the synthesised material was examined. Further, the partial ionic exchange of Ba ions in BaZrO3 was attempted to synthesise Cs modified BaZrO3 . Characterisation results revealed the synthesis of phase pure and strongly basic materials. BaZrO3 was tested as a transesterification catalyst for the synthesis of biodiesel. Transesterification reaction variables for BaZrO3 catalysed transesterification were optimised using response surface methodology based Box-Behnken designing approach. Under the suggested optimal conditions the predicted conversion was 94.12%, and the experimentally determined conversion of 93.2 ± 0.3% confirmed the validity of the generated quadratic model. Cs modification of BaZrO3 enhanced its basic strength. Under the optimised conditions for pristine BaZrO3, the effect of Cs modification on BaZrO3 was assessed, and it led to a conversion of 97.27 ± 0.4%. Both the materials were effective in catalysing the transesterification of M. pinnata oil, however; only Cs-BaZrO3 catalysed oil met the EN 14214:2003 specification for minimum ester content in biodiesel. Graphical abstract: Image Highlights: BaZrO3 and Cs-BaZrO3 were synthesised through relatively mild solid-state route. Synthesised materials were used as catalysts for transesterification of Karanja oil. Reaction variables were optimised using Box-Behnken designing. BaZrO3 and Cs-BaZrO3 led to a conversion of 93.27% and 97.27% respectively. Cs impregnation of Perovskite BaZrO3 was found to be an effective strategy.